Current Issues of Cluster Operation in the Southern Great Plain Region - Kovács, Helga (Current social and economic processes / Jelenkori Társadalmi és Gazdasági Folyamatok, 2022)
During the research I examined the clusters operating in the Southern Great Plain. First, I analyzed the concept and key characteristics of clusters. In the following, I have briefly summarized the short history of the clusters in Hungary and then in the Southern Great Plain, the reason for their formation and the most important characteristics. I visited the Southern Great Plain clusters on the basis of the database of the International and Cluster Department within the Managing Authority of the Ministry of Finance, Economic Development Programs and the Public Benefit Association of the Southern Great Plain Regional Innovation Agency. I first used an online questionnaire to ask cluster managers about the main characteristics and activities of clusters. The questionnaire helped to filter out clusters that are engaged in real economic activity. I conducted a semi-structured interview with these clusters. Twelve clusters participated in the completion of the online questionnaire, and then seven clusters were relevant for further research. The study shed light on the main factors influencing the successful operation of the clusters, as well as the factors that make their operation difficult and impossible. The results obtained during the research were summarized in the form of a SWOT-analysis.